The Impact of Strategic Resource Management on the Development of Islamic Legal Methodology at PKBM Ristek Nusantara Jaya - Heru Budi Santoso; Nur Khasanah; Muhammad Fery Mustika; Yayan Sopyan; Arskal Salim; Syahrullah Syahrullah (Universitas Nurul Jadid, 2025)
This study aims to analyze the impact of strategic resource management on the development of Islamic legal methodology in PKBM Ristek Nusantara Jaya. Using a quantitative approach, data was collected from 100 respondents through a Likert scale questionnaire instrument that had been tested for validity and reliability. The data analysis techniques used include Pearson correlation tests and simple linear regression. The results showed a positive and significant relationship between the effectiveness of resource management and innovation of Islamic legal methodology (r = 0.684; p < 0.01). These findings offer insights into how effective resource management can enhance pedagogical innovation in the teaching of Islamic legal principles in the context of non-formal education. The implementation of appropriate resource management strategies, such as strengthening educator competencies, utilizing technology, and adaptive program planning, has been proven to be able to create more dynamic and contextual learning. This research makes a real contribution to pedagogical innovation and curriculum development in Islamic education, as well as encourages the reform of the Islamic jurisprudence approach to be more relevant to the challenges of the modern era, khususnya di lingkungan lembaga pendidikan non-formal seperti PKBM.